The kinetochore protein Cenp-F is a potential novel target for zoledronic acid in breast cancer cells - Brown, Hannah K (Blackwell Publishing Ltd, 2011)
The anti-resorptive agent zoledronic acid inhibits key enzymes in the mevalonate pathway, disrupting post-translational modification and thereby correct protein localization and function. Inhibition of prenylation may also be responsible for the reported anti-tumour effects of zoledronic acid, but the specific molecular targets have not been identified. Cenp-F/mitosin, a kinetochore-associated protein involved in the correct separation of chromosomes during mitosis, has been shown to undergo post-translational prenylation and may therefore be a novel target contributing to the anti-tumour effects of zoledronic acid. We investigated whether zoledronic acid causes loss of Cenp-F from the kinetochore in breast cancer cells, to determine if the reported anti-tumour effects may be mediated by impairing correct chromosome separation. MDA-MB-436, MDA-MB-231 and MCF-7 breast cancer cells and MCF-10A non-malignant breast epithelial cells were treated with zoledronic acid in vitro, and the effect on Cenp-F localization was analysed by immunoflourescence microscopy. Zoledronic acid caused loss of Cenp-F from the kinetochore, accompanied by an increase in the number of cells in pro-, /prometa- and metaphase in all of the cancer cell lines. There was also a significant increase in the number of lagging chromosomes in mitotic cells. The effects of zoledronic acid could be reversed by inclusion of an intermediary of the mevalonate pathway, showing that the loss of Cenp-F from the kinetochore was caused by the inhibition of farnesylation. In contrast, no effect was seen on Cenp-F in non-malignant MCF-10A cells. This is the first report showing a specific effect of zoledronic acid on a protein involved in the regulation of chromosome segregation, identifying Cenp-F as a potential new molecular target for NBPs in tumour cells.